2019
DOI: 10.1080/02670844.2019.1653596
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment and deposition of alumina in metallic microchannels

Abstract: The objective of this work is the generation of a suitable surface, in microchannels of AISI 304 stainless steel for the manufacture of a microreactor, which ensures the anchoring of the active phase. The novelty of the work lies in achieving stabilization layer to work in different environments. The roughness generation was carried out by thermal treatment and passivation via alumina deposition by the impregnation method. The characterization was made with SEM-EDX and confocal microscope images. In a humid at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Generally, a fluid located on a planar solid surface will produce a specific angle of contact between the solid and fluid [17][18][19]. The contact angle made by the fluid droplet over different surfaces like a flat surface, wire [20,21], and tube [22] were calculated and reported. The majority of the research carried out in the area of boiling of nanofluid has reported an increase in critical heat flux (CHF) due to the decrease in contact angle (enhanced surface wettability).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a fluid located on a planar solid surface will produce a specific angle of contact between the solid and fluid [17][18][19]. The contact angle made by the fluid droplet over different surfaces like a flat surface, wire [20,21], and tube [22] were calculated and reported. The majority of the research carried out in the area of boiling of nanofluid has reported an increase in critical heat flux (CHF) due to the decrease in contact angle (enhanced surface wettability).…”
Section: Introductionmentioning
confidence: 99%